EFEKTIVITAS AWIG-AWIG DALAM KELESTARIAN LINGKUNGAN HIDUP POHON DI DESA ADAT TENGANAN PEGRINGSINGAN, KECAMATAN MANGGIS, KABUPATEN KARANGASEM - Ni Kadek Dwi Mertaning Astiti; Anak Agung Putu Wiwik Sugiantari (Jurnal Hukum Mahasiswa, 2023)
The purpose of this study was to determine the effectiveness of awig-awig in environmental sustainability of trees in the Tenganan Pegringsingan Traditional Village, Manggis District, Karangasem Regency. The type of legal research used is the empirical legal research method. The results of this study are that the procedures and mechanisms for implementing awig-awig have been carried out from ancient times without direct socialization. This is due to being socialized from generation to generation only in the family environment. The effectiveness of awig- awig regarding environmental preservation of trees can be seen from the fact that most people know about awig-awig. In practice, the awig-awig has not been fully effective due to a lack of supervision from village enforcers and a lack of awareness from the village community.